2019
DOI: 10.3390/nu11061283
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Adherence is Associated with Lower Prevalence of Functional Gastrointestinal Disorders in Children and Adolescents

Abstract: Dietary patterns may have a role in the prevention of functional gastrointestinal disorders (FGIDs). The current study aimed at examining the association between FGIDs and adherence to the Mediterranean diet (MD) among elementary school children (ESC), as well as high school students (HSS). In a prospective cohort study, data from 1116 subjects (387 ESC and 448 HSS) aged 6–18 years were collected. FGID identification was based on the Questionnaire on Pediatric Gastrointestinal Symptoms-Rome III (QPGS-RIII). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 48 publications
5
28
0
4
Order By: Relevance
“…Apesar dos benefícios associados a fibra para a saúde humana, a maioria dos adultos e crianças não atingem às recomendações [13]. Embora a relação de causa e efeito entre dieta e a constipação intestinal funcional ainda seja controversa, os efeitos da dieta no hábito intestinal são cruciais na terapêutica da constipação e a adesão a determinados padrões alimentares pode diminuir significativamente os sintomas dessa condição [5][6][7][8][9][10][11][12][13][14]. da fibra alimentar ingerida foi obtida de produtos ultraprocessados [16].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Apesar dos benefícios associados a fibra para a saúde humana, a maioria dos adultos e crianças não atingem às recomendações [13]. Embora a relação de causa e efeito entre dieta e a constipação intestinal funcional ainda seja controversa, os efeitos da dieta no hábito intestinal são cruciais na terapêutica da constipação e a adesão a determinados padrões alimentares pode diminuir significativamente os sintomas dessa condição [5][6][7][8][9][10][11][12][13][14]. da fibra alimentar ingerida foi obtida de produtos ultraprocessados [16].…”
Section: Discussionunclassified
“…A dieta do mediterrâneo é reconhecida por ser saudável, os pratos nessa alimentação são ricos em fibras e antioxidantes, além do baixo teor de gorduras saturadas. A prevalência de FGIDs (Distúrbios Gastrointestinais Funcionais) em crianças e adolescentes é associada a uma menor adesão a dieta do mediterrâneo [27] As crianças, em geral, são mais seletivas nas escolhas dos alimentos e, habitualmente, apresentam um consumo reduzido de fibras alimentares [28]. As crianças com constipação funcional desenvolvem um comportamento alimentar não saudável que por sua vez aumenta o risco da doença caracterizando um ciclo vicioso [29].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In Greece, a school-based, cross-sectional study showed that reduced fish and increased junk food consumption were related to a higher likelihood of developing functional abdominal pain disorders [ 36 ]. Another study concluded that good adherence to the Mediterranean diet is associated with a lower prevalence of FGIDs [ 37 ]. The Mediterranean diet is centered on whole grains, fruits, vegetables, beans, herbs, spices, nuts and healthy fats such as olive oil.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Poor nutrition, for example, consumption of highly processed and "fast" foods, has been implicated in FGID etiology [17,18]. Conversely, a Mediterranean diet has been associated with a lower prevalence of FGID [19]. A dietary therapeutics approach, for example a low-FODMAP diet in which rapidly fermentable carbohydrates that are poorly absorbed by the gut are eliminated or avoided as much as possible, is a typical dietary protocol for IBS patients [20].…”
Section: Introductionmentioning
confidence: 99%